Two-dimensional flow quantitative MRI of aortic arch blood flow patterns: Effect of age, sex, and presence of carotid atheromatous disease on prevalence of spiral blood flow - Houston, J. Graeme; Gandy, Stephen J.; Sheppard, Declan G.; Dick, John B.; Belch, Jill J.F.; Stonebridge, Peter A. (Journal of magnetic resonance imaging, 2003)
Purpose: To determine the effect of age, sex, and presence of carotid atheromatous disease on the presence of aortic spiral blood flow pattern using two‐dimensional flow quantitative magnetic resonance imaging (MRI). Materials and Methods: Sixty subjects (37 women, 23 men) were examined. Prospective phase contrast flow quantitative MRI (1.5 T, Siemens Symphony) sequences in the plane of the aortic arch, and three‐dimensional contrast‐enhanced MR angiography of the vessels from the aortic arch to the circle of Willis, were performed. Flow quantitative analysis, using circular regions of interest, in the root, apex, and descending aortic arch to determine the presence of a spiral blood flow pattern was undertaken. The results were correlated with the subjects age, sex, and presence of significant carotid arterial disease. Results: A spiral blood flow pattern was seen during diastole in 43 of 50 (86%), 42 of 48 (88%), and in 26 of 28 (93%) subjects in the root, apex, and descending aortic arch, respectively. Spiral flow was seen during systole in 14 of 35 (40%), 20 of 47 (42%), and 11 of 31 (35%) subjects in the root, apex, and descending aortic arch, respectively. There was no clear effect of age or sex on the presence of spiral flow. Carotid disease was associated with a significant reduction in the prevalence of systolic spiral flow from 51%–19% subjects (P < 0.05). Conclusion: Spiral flow pattern can be seen in the arch of the aorta in clinical practice using flow quantitative MRI. The prevalence of spiral flow pattern does not appear affected by subject age or sex. Carotid atheromatous disease is associated with a reduction in prevalence of systolic spiral flow pattern in the aortic arch. J. Magn. Reson. Imaging 2003;18:169–174. © 2003 Wiley‐Liss, Inc.